Ethiopia - Rural Income Diagnostics Study : Leveraging the Transformation in the Agri-Food System and Global Trade to Expand Rural Incomes - World Bank (Washington, DC, 2022)
Ethiopia began the decade on a great run, with high economic growth and significant gains in poverty reduction nationally. But the gains were unevenly shared. Multiple shocks at the beginning of the new decade threaten to discontinue progress and possibly undo most of the gains made in the recent past. This rural income diagnostics (RID) study seeks to inform how to promote growth in rural incomes to accelerate poverty reduction. The objective of the RID is to examine how those who currently reside in rural areas can have higher incomes in the future, which can entail one or more members moving to urban areas. The focus is on income growth that results in higher incomes on average, but also income that is less volatile because of due consideration to effective risk reduction and management, and to ensuring that growth is sustainable. While the RID focuses only on income that is earned by rural households, it is much more detailed in its identification of the constraints because of this narrower focus. The diagnostic provides evidence to validate constraints and key areas of focus in ongoing agriculture and rural policy reforms and other relevant reforms under the Homegrown Economic Reform Agenda (HGERA), elevate the importance of some reforms where immediate action is required, and provide empirical arguments to support important policy interventions where consensus may be lacking or there is policy hesitation.